Body shaming and internalized weight bias as potential precursors of eating disorders in adolescents - Cerolini, Silvia; Vacca, Mariacarolina; Zegretti, Anna; Zagaria, Andrea; Lombardo, Caterina (Frontiers in Psychology, 2024)
Introduction Body shaming (BS) is a growing phenomenon within the school context, especially among adolescents. Recently, it has been described as an unrepeated act in which a person expresses unsolicited, mostly negative comments about an individual’s body. The targeted person perceives these comments as negative, offensive or body shame-inducing. Empirical evidence also suggests that body weight is the most common reason that youths are teased and bullied. Indeed, weight stigma, described as bias or discriminatory behaviors, attitudes, feelings, and thinking about individuals, because of their weight, can lead to weight-based discrimination and victimization. Preliminary evidence suggests that BS and weight stigma have negative effects on psychological health both in the short and long term. In the delicate stage of adolescence development and pubertal maturation, BS experiences can be highly prevalent and it can lead to adverse outcomes such as eating disorders (ED). However, prevalence data in the Italian context are still lacking. Methods The study aims to estimate weight-related BS perceived by different sources (i.e., peers and family members) and their associations with public and internalized weight bias, body mass index (BMI), body dissatisfaction, and ED symptoms. A sample of 919 high school students (Mage = 15.97, SD = 1.58; 57.1% boys) completed a battery of self-report questionnaires assessing these variables. Results One in four students reported experiences of weight-related BS by peers or family members. A total of 37% reported having at least one BS experience in a lifetime. Higher scores of ED symptoms, body dissatisfaction, and weight bias were reported by adolescents who experienced BS, especially females. Among overweight participants, results showed that internalized weight bias partially mediated the relationship between BS by family members and ED symptoms and fully mediated the relationship between BS by peers and ED symptoms, after controlling for age, sex and BMI. Discussion These findings, despite their cross-sectional nature, add an important contribution to the creation of quantitative empirical evidence on the phenomenon of BS. Its role in explaining eating disorders, both alone and with the mediation of internalized weight stigma has been first proved and needs to be confirmed by longitudinal results.